Effects of anti-skid rubber mat on behaviour, stress level and milk yield in dairy cows - Abdul Talib, Madihah (2020)
In the present study, the effects of anti-skid rubber mat on the behaviour, stress level and milk yield of dairy cows were evaluated. Forty dairy cows from two anti-skid rubber mat (RM)-enriched farms (n=20) and two concrete flooring (CF) farms (n=20) were selected for the study. The lying, standing, walking, feeding and drinking behaviour of these cows were recorded for two hours daily for five days and further analysed off-line using the Solomon Coder© software. Results showed that cows reared on RM have a significantly higher (p<0.05) frequency and duration (sec) of lying behaviour compared to cows reared on CF, with values (mean ± SD) of 4.96 ± 1.33 and 3950.75 ± 744.48 (RM farms) versus 2.26 ± 1.29 and 1959.6 ± 762.84 (CF farms). However, the frequency and duration (sec) of standing behaviour were significantly higher for CF farms (CF: 6.22 ± 1.66 and 4082.73 ± 775.46 versus RM: 4.10 ± 1.49 and 2388.42 ± 801.11). A retrospective analysis of the average milk yield of cows reared on RM (n=20) indicated a significantly higher milk yield (17.8 ± 0.84 L) than cows reared on CF farms (n=20) (7.55 ± 0.72 L), p<0.05. Results from the glucose tolerance test (GTT), adrenocorticotropic hormone (ACTH)-challenge and total white blood cell count conducted on five random cows from each RM and CF farm were not significantly different. However, data from the adrenocorticotropic hormone (ACTH)-challenge showed that the average basal concentration level of cortisol in cows from CF farms was significantly higher (p<0.05) compared to cows reared on RM (38.1 ± 23.9 ng/ml versus 17.2 ± 10.8 ng/ml), indicating a higher level of stress. In conclusion, the anti-skid rubber mat encourages the natural behaviour of dairy cows such as lying and an improvement in milk yield without significant effect on the stress levels of the cows under study. However, since many factors contribute to the production of milk, it is recommended that future studies include other parameters such as environmental factors, management systems, types and duration of rubber mats used, in addition to nutritional and feed intake of cows from each farm.